The Development of Science Learning Achievement and Teamwork Skills of Fifth Grade Students through Using the 5E Learning Model and Online Games - Amprawet, Niracha (An Online Journal of Education, 2026)
The research aimed to compare the science learning achievement and teamwork skills of fifth-grade students before and after learning through the 5E learning model and online games. The sample consisted of one classroom of 30 fifth-grade students in the first semester of the 2025 academic year from a school in Nakhon Nayok province, using cluster random sampling with the classroom as the unit of sampling. The research instruments included: 1) lesson plans for the 5E learning model and online games with the average IOC value of 1.00, 2) a science learning achievement test with a reliability value of 0.74, and 3) a teamwork skills observation form with the average IOC value of 1.00. The statistics used for data analysis included mean, standard deviation, and t-test for dependent samples. The research findings indicate that: 1) the sample had a post-test science learning achievement score higher than the pre-test score, with statistical significance at the .05 level (M = 15.00, SD = 1.97) and 2) the sample had a post-test teamwork skills score higher than the pre-test score, with statistical significance at the .05 (M = 6.40, SD = 0.75). The findings suggest that instructors should consider integrating online games featuring point systems or leaderboards into the Elaboration phase of the 5E instructional model. Furthermore, for content requiring analytical thinking, games should be utilized as a medium for simulations. This approach can stimulate collaborative problem-solving among learners and ultimately enhance academic achievement.